Spontaneous emission by an ensemble of dipoles coupled to a plasmonic nanoresonator. Issue 15 (2nd September 2019) - Uzodinma, J.; Nelson, N.; Dai, Q.; Shahbazyan, T. V.
ABSTRACT: Spontaneous emission from ensembles of quantum emitters (QEs) such as atoms, molecules or semiconductor quantum dots can be greatly enhanced by cooperative effects arising from electromagnetic correlations. We describe a cooperative mechanism for emission of light by an ensemble of QEs based upon cooperative energy transfer from QEs to localized surface plasmons in metal-dielectric structures followed by plasmon radiation at a rate that scales with the ensemble size. For large QE ensembles saturating the plasmon mode volume, we derive universal, i.e. independent of local field distribution, expression for cooperative Purcell factor that can by far exceed the field enhancement limits for individual QE in a hot spot. We also derive radiated power spectrum that retains the plasmon resonance lineshape and, in contrast to common cooperative mechanisms, is insensitive to natural variations of QEs' emission frequencies.